MODEL PENILAIAN PENDIDIKAN KARAKTER OLEH GURU DI SMP BOARDING SCHOOL â€œPUTRA HARAPANâ€ PURWOKERTO - Istiana, Janatun (Penerbit CV Tentrem Karya Nusa, 2019)
Abstract: The negative impact of globalization now makes Indonesian people forget the national character. The role of schools that work with families and communities is very much needed to instill strong character in children who are future leaders of the nation. In order to assess the results of implementing character education in schools,